2009
DOI: 10.1126/science.1167000
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Chromosome Bi-Orientation by Spatial Separation of Aurora B Kinase from Kinetochore Substrates

Abstract: Successful cell division requires that chromosomes attach to opposite poles of the mitotic spindle (bi-orientation). Aurora B kinase regulates chromosome-spindle attachments by phosphorylating kinetochore substrates that bind microtubules. Centromere tension stabilizes bi-oriented attachments, but how physical forces are translated into signaling at individual centromeres is unknown. Using FRET-based biosensors to measure localized phosphorylation dynamics in living cells, we found that phosphorylation of an A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
610
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 494 publications
(653 citation statements)
references
References 23 publications
37
610
2
1
Order By: Relevance
“…Aurora B localizes prominently to the centromere region of mitotic chromosomes and it has been suggested that a gradient of Aurora B kinase originating from the centromere can only 'reach' outer kinetochore substrates such as Hec1 when sister kinetochores are under low tension (Tanaka et al, 2002;Andrews et al, 2004;Pinsky et al, 2006). In support of this, a recent study found that phosphorylation of an engineered Aurora B substrate at the kinetochore was dependent on its distance from the centromere and, furthermore, that experimentally positioning Aurora B closer to the outer kinetochore prevented stabilization of bi-oriented kinetochore-MT attachments (Liu et al, 2009). In regard to Aurora B phosphorylation of Hec1 specifically, our results are not fully consistent with a spatial positioning model for two reasons.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Aurora B localizes prominently to the centromere region of mitotic chromosomes and it has been suggested that a gradient of Aurora B kinase originating from the centromere can only 'reach' outer kinetochore substrates such as Hec1 when sister kinetochores are under low tension (Tanaka et al, 2002;Andrews et al, 2004;Pinsky et al, 2006). In support of this, a recent study found that phosphorylation of an engineered Aurora B substrate at the kinetochore was dependent on its distance from the centromere and, furthermore, that experimentally positioning Aurora B closer to the outer kinetochore prevented stabilization of bi-oriented kinetochore-MT attachments (Liu et al, 2009). In regard to Aurora B phosphorylation of Hec1 specifically, our results are not fully consistent with a spatial positioning model for two reasons.…”
Section: Discussionmentioning
confidence: 94%
“…Under this experimental condition, active Aurora B kinase remains at the outer kinetochore, indicating that although the kinase is spatially positioned to rephosphorylate Hec1, it does not. Because it is probable that other outer kinetochore targets are regulated by spatial positioning of the kinase (Liu et al, 2009;Liu et al, 2010;Welburn et al, 2010), the mechanism controlling Aurora-Bdependent phosphorylation cycles might differ between kinetochore targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[36][37][38] Once chromosomes become bi-oriented and tension is applied between sister kinetochores, Ndc80 moves away from Aurora B, resulting in kinetochoremicrotubule attachment stabilization. 39,40 Here we elaborate on recent studies that demonstrated a role of Dynein, 5 chromokinesins 5,41 and Aurora A kinase 5,41,42 in the prevention and correction of erroneous kinetochore-microtubule attachments during chromosome congression.…”
Section: Introductionmentioning
confidence: 99%
“…Aurora B kinase and Mps1 are at the top of this pathway and they are thought to regulate each other, [20][21][22][23] the downstream components Bub1, BubR1, Bub3, Mad1 and Mad2 form 3 complexes: Bub1-Bub3, BubR1-Bub3 and Mad1-Mad2. 24 They are recruited to kinetochores in a KMN-dependent manner, [25][26][27] and when the kinetochore is unattached, the checkpoint is activated.…”
Section: Introductionmentioning
confidence: 99%